Peran Kelompok Wanita Tani Dalam Perekonomian Masyarakat Desa Neglasari Kabupaten Bogor - Arviana Ahmad Evendi; Prayoga Suryadharma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The potential of rural agricultural products in Neglasari Village needs to be addressed with an activity that involves women in utilizing agricultural products and managing the surrounding environment through women's farmer groups (KWT). This activity aims to knowing the extent of the role of KWT members in the economy of Neglasari Village. This activity is carried out by the observation method. The method of observation is directly to the village community to obtain information about agriculture, agricultural products to the marketing of agricultural products in Neglasari village, as well as obtain information about groups of women farmers in the village. This activity as a whole can be said to be good and successful. The conclusion in this activity was that the Farmer Women Group in Neglasari village made added value from an agricultural product by making an activity to process agricultural products such as making banana chips and cassava chips. That is expected to improve the skills of mothers and increase income for families, the family economy can increase. Keywords: agricultural products, economy, women's farmer groups